PENENTUAN KADAR LUNACRIDINE PADA EKSTRAK KAYU SANREGO (LUNASIA AMARA BLANCO) YANG DIEKSTRAKSI DENGAN METODE MASERASI DAN REFLUKS - Alyidrus, Rugayyah (Jurnal Ilmiah As-Syifaa, 2017)
Determination of the research done on the extract lunacridine Sanrego (L. amara Blanco) in extraction with various methods of extraction. This study aims to determine the various menthods of extraction (maceration, refluks and soxhletasi) are most appropriate to extractim sanrego lunacridine on wood extract (L. amara Blanco) and determine the levels with TLC-Densitometry. Wood sanrego (L.amara Blanco) extrac dusing methanol solvent. Lunacridine as marker and sample in TLC and eluted wiyh the eluent n-hexane:ethyl acetate (2:8) and then scanned with a TLC-Densitometry of wavelength 303 nm. The results showed that the most appropriate extraction method is refluks with quote lunacridine content 37,52 µg/µL  that in maceration 35,03 µg/µL .